Competing and interrelated conceptions of equality in Kenya's 2010 constitution - Miyandazi, V (2018)
This thesis explores the ways in which competing and interrelated conceptions of equality in Kenya’s 2010 Constitution should be conceptualised, interpreted and applied. Kenyans’ overwhelming support for the adoption of the 2010 Constitution signalled a rebirth of the nation with a strong emphasis on equality and redressing past injustices. For this reason, the document has been termed as ‘transformative’, ‘historic’ and ‘revolutionary’ as it seeks to fundamentally change the social, political and economic way of life of all Kenyans. The entrenchment of multiple equality provisions not guaranteed in the previous Constitution establishes a crucial constitutional framework for addressing inequalities. However, more decisive still is how well the 2010 Constitution’s equality provisions continue to be conceptualised, interpreted and applied. The Constitution contains different articulations of equality, both in the equality clause (Article 27) and elsewhere in the Constitution. These provisions reflect different, sometimes complementary and other times potentially conflicting, conceptions of equality. Yet, current equality jurisprudence says little, if anything, on how the multiple and competing conceptions of equality in the Constitution should be harmoniously interpreted. The concept remains open-textured, which offers limited guidance to legal practitioners and other pertinent players on what is required of them by law in addressing inequalities. This thesis aims to provide more clarity in this area of law in Kenya by examining all the equality principles in the Constitution with a specific emphasis on the potentially conflicting issues, with the aim of attempting to find a coherent and mutually supportive way of understanding the broader conception of equality in the Constitution. Two principled approaches are proposed for the harmonious interpretation of the Constitution’s equality concepts; the equal concern and respect approach and the multi-dimensional equality approach.